2009
DOI: 10.1080/07357900902897557
|View full text |Cite
|
Sign up to set email alerts
|

CD10 AND CD34 EXPRESSION IN CHILDHOOD ACUTE LYMPHOBLASTIC LEUKEMIA IN MOROCCO: Clinical Relevance and Outcome

Abstract: CD10 and CD34 expression in 86 Moroccan children with acute lymphoblastic leukemias (ALL) and the relevance to prognosis, diagnosis, and outcome during a 5-year follow-up were examined. At diagnosis, 57% of patients had CD10(+) blasts, while 35% had CD34(+) blasts. The CD10(+) blast frequency was much higher (80%) in B-ALL than in T-ALL (20%). The frequency of CD34(+) blasts was higher in B-ALL (48%) compared to T-ALL (16%). The 5-year survival curves showed that children with CD10(+) B-ALL had a significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 39 publications
6
30
1
Order By: Relevance
“…A study conducted by Dakka et al, found that the five years survival rate for the CD10 − CD34 − group was only 22% [10]. In our study, lack of both CD10 and CD34 expression was also related to worse prognosis; OS was 61% in the combination CD10 + and/or CD34 + group vs. 31% in the double negative group, p<0.001 ( Figure 1C).…”
Section: Overall Patientssupporting
confidence: 52%
See 4 more Smart Citations
“…A study conducted by Dakka et al, found that the five years survival rate for the CD10 − CD34 − group was only 22% [10]. In our study, lack of both CD10 and CD34 expression was also related to worse prognosis; OS was 61% in the combination CD10 + and/or CD34 + group vs. 31% in the double negative group, p<0.001 ( Figure 1C).…”
Section: Overall Patientssupporting
confidence: 52%
“…Studies on the expression of CD10 and CD34, alone or in combination, as a prognostic factor, found discrepancies [6,7,10,10,22,23]. These discrepancies may be dependent upon sensitivity of the immunophenotyping, upon patient variables, or upon differences in treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations